PERBANDINGAN KEMAMPUAN REPRESENTASI DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK PADA SISWA YANG MENDAPAT PEMBELAJARAN KOOPERATIF DISERTAI QUANTUM LEARNING DENGAN SISWA YANG MENDAPAT PEMBELAJARAN KONTEKSTUAL DITINJAU DARI KEMAMPUAN AWAL SISWA - Wicaksono, Bintang; Mardiyana, Mardiyana; Sutrima, Sutrima (Jurnal Pembelajaran Matematika, 2013)
Abstract: The objectives of this research are to investigate the effect of learning models on representation and mathematical problem solving ability viewed from the student prior knowledge. The learning models compared were cooperative combined with quantum learning and contextual learning. The samples of this research were taken by using stratified cluster random sampling technique. The populations were all of the students in grade VII of State Primary Schools in Sukoharjo regency 2012/2013. The number of the samples was 142 students, in which 72 students in the experimental class one, and 72 students in the experimental class two. The instrument used to collect the data were test of the representation ability and test of the problem solving ability. The data was analyzed by using multivariate analysis of variance. The results of the research are: (1) the students taught by using contextual learning have better on both the representation and the mathematical problem solving ability than the students taught by using cooperative combined with quantum learning, (2) the students having high prior knowledge category have better on both the representation and the mathematical problem solving ability than the students having medium prior knowledge category, and the students having medium priorÂ knowledge category have better on both the representation and the mathematical problem solving ability than students having low prior knowledge category, (3) there was no interactions between the learning model and the prior knowledge toward the studentsâ representation and mathematical problem solving ability. It means that the use of either of contextual learning model or cooperative combined with quantum learning model, the students having high prior knowledge category have better on both the representation and mathematical problem solving ability than the students having Â mediumÂ prior knowledge category, and the students having medium prior knowledge category have better on both the representation and the mathematical problem solving ability than the students with low prior knowledge category. The students having high, medium, or the low prior knowledge taught by using contextual learning have better on both the representation and the mathematical problem solving ability than the students taughtÂ by using cooperative combined with quantum learning. Keywords: cooperative combined with quantum learning, contextual learning, students prior knowledge, representation ability, mathematical problem solving ability.